Serum levels of miRNA-21-5p in vitiligo patients and effects of miRNA-21-5p on SOX5, beta-catenin, CDK2 and MITF protein expression in normal human melanocytes. Issue 1 (January 2021) - Aguennouz, M'Hammed; Guarneri, Fabrizio; Oteri, Rosaria; Polito, Francesca; Giuffrida, Roberta; Cannavò, Serafinella P.
Highlights: The expression of serum miR-21-5p in vitiligo patients is significantly increased. Serum miR-21-5p is directly and significantly correlated with vitiligo severity. SOX5 protein expression in melanocytes decreases after trasfection with miR-21-5p. Upregulation of miR-21-5p might be a tentative compensation mechanism in vitiligo. Current knowledge of the pathogenesis of vitiligo is probably incomplete. Abstract: Background: Epigenetics of vitiligo was evaluated in few studies. In particular, the role of miR-21, a microRNA involved in various processes, including melanogenesis, was never investigated. Objective: Evaluation of serum levels of miR-21-5p in vitiligo patients and miR-21-5p effects on melanogenesis. Methods: We measured serum levels of miR-21-5p in 40 patients affected by nonsegmental vitiligo and 40 sex- and age-matched healthy controls. Next, normal human melanocytes were transfected with miR-21-5p to study the effects of this microRNA, which targeted some proteins involved in melanogenesis pathway like SOX5, beta-catenin, cyclin-dependent kinase 2 (CDK2), and MITF. Results: The expression of miR-21-5p in vitiligo patients was 3.6–4454.4 fold (mean 990.4 ± 1397.9) higher than in controls. The relative expression of miR-21-5p was directly and significantly correlated with disease severity, defined by VASI (Vitiligo Area and Severity Index) score (Rho = 0.89, p = 10 −7 ), but not other individual or clinical characteristics. In the second part of the study, a significant reduction of SOX5, beta-catenin and CDK2 protein expression and increase of MITF protein expression was observed in cultured melanocytes after 24 h trasfection with miR-21-5p. Conclusion: According to literature, miR-21-5p upregulation and consequent SOX5 downregulation should upregulate melanogenesis, while vitiligo is characterized by skin depigmentation. Our results suggest that current knowledge of the pathogenesis of vitiligo is probably incomplete. Clinical manifestations could result from an altered balance between metabolic pathways with contrasting effects. In this view, miR-21-5p upregulation might be a tentative compensation mechanism. Further studies appear necessary to confirm and better understand our results and their importance.